Malononitrile: A Versatile d1-Synthon for the Synthesis of Hetero-aromatic Carboxylic Acid Derivatives - Brünjes, Marco; Ford, Mark James; Dietrich, Hansjörg; Wilson, Kirsty (Synlett, 2015)
A convenient one-pot synthesis of heteroaromatic carboxylic acid derivatives from malononitrile substituted heteroaromatic compounds, namely pyridines, pyrimidines, and 1,3,5-triazines is described. In this procedure, the oxidation of malononitriles with anhydrous m-CPBA, followed by addition of different nucleophiles (alcohols, amines, thiols) under anhydrous conditions afforded the corresponding carboxylic acid derivatives in good to excellent yields.
Keywords: malononitrile; oxidation; m-CPBA; carboxylic acids; heterocycles